1988
DOI: 10.1016/0014-5793(88)81014-7
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvate kinase type M2 is phosphorylated at tyrosine residues in cells transformed by Rous sarcoma virus

Abstract: Chicken embryo cells (CECs) contain pyruvate kinase (PK) type M~ (M2-PK). Transformation of CECs by Rous sarcoma virus (RSV) leads to a reduction in the affinity of PK for the substrate phosphoeno/pyruvate. In vitro, M2-PK can be phosphorylated at tyrosine residues by pp60 v-~, the transforming protein of RSV. To study tyrosine phosphorylation of M2-PK in intact RSV-transformed cells, the protein was immunoprecipitated from a2P-labeled normal and RSV-SR-Atransformed CECs. Phosphoamino acid analysis of immunopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 22 publications
(14 reference statements)
0
50
0
Order By: Relevance
“…These findings indicate that control of glycolytic flux through PKM2 activation/inactivation may be important for tumor growth in some indications. Cancer cells inactivate PKM2 through multiple mechanisms, including oncoprotein binding (14,15), tyrosine phosphorylation (16)(17)(18), lysine acetylation (19), cysteine oxidation (20), and prolyl hydroxylation (21). In each case, decreased PKM2 activity correlates with increased tumorigenicity.…”
Section: Introductionmentioning
confidence: 99%
“…These findings indicate that control of glycolytic flux through PKM2 activation/inactivation may be important for tumor growth in some indications. Cancer cells inactivate PKM2 through multiple mechanisms, including oncoprotein binding (14,15), tyrosine phosphorylation (16)(17)(18), lysine acetylation (19), cysteine oxidation (20), and prolyl hydroxylation (21). In each case, decreased PKM2 activity correlates with increased tumorigenicity.…”
Section: Introductionmentioning
confidence: 99%
“…Further attempts to identify spots involved in hypoxia-induced responses must be confirmed also by direct microanalytical characterization; experiments are in progress to identify spots using protein sequencing and/or mass spectrometric techniques. Several observations can be positively interpreted: (a) as expected, proteins identified by gel comparison with a human 2-D reference map involved "housekeeping" and/or well conserved protein species; (b) most identified spots positive to anti-PY antibodies resulted as either known tyrosinephosphorylated proteins, e.g., tubulin (MacRae, 1997), HSC70 (Egerton et al, 1996), and pyruvate kinase (Presek et al, 1988), or tyrosine-phosphorylation sites containing proteins, as predicted by the ScanPROSITE algorithm (see Materials and Methods); and (c) as expected, several identified proteins containing no tyrosinephosphorylation site resulted as nonimmunoreactive spots (e.g., NADH-ubiquinone dehydrogenase 24-kDa subunit).…”
Section: Table 1 Description Of Immunoreactive Spotsmentioning
confidence: 66%
“…Other studies have shown that M2-PK activity in tumor cells is also regulated by the direct interaction of M2-PK with several oncoproteins. The transforming factor of Rous sarcoma virus, pp60v-src kinase, has tyrosine kinase-specific activity and phosphorylates M2-PK at a tyrosine residue to reduce M2-PK activity (23,36). The serine/threonine kinase A-Raf directly binds to M2-PK to regulate the pyruvate kinase (25).…”
Section: Discussionmentioning
confidence: 99%